2011
DOI: 10.1038/nrn2948
|View full text |Cite
|
Sign up to set email alerts
|

Protein scaffolds in the coupling of synaptic exocytosis and endocytosis

Abstract: Communication between nerve cells largely occurs at chemical synapses -specialized sites of cell-cell contact where electrical signals trigger the exocytic release of neurotransmitter, which in turn activates postsynaptic receptor channels. The efficacy with which such chemical signals are transmitted is crucial for the functioning of the nervous system. Modulation of neurotransmission enables nerve cells to respond to a vast range of stimulus patterns. Synaptic activity can also be tremendously diverse; from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

12
246
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 249 publications
(262 citation statements)
references
References 121 publications
(200 reference statements)
12
246
0
Order By: Relevance
“…Previous analysis in this model examined the temperature-sensitive (TS) DYNAMIN mutant shibire and revealed a rapid role for endocytic mechanisms in maintaining neurotransmitter release during synaptic activity (15,16). Subsequent work has extended these findings and showed that inhibition of DYNAMIN or AP-2 disrupts fast refilling of the release-ready synaptic vesicle pool (17)(18)(19). The results reported here demonstrate colocalization of CLATHRIN and DAB at the active zone (AZ) and provide functional and ultrastructural evidence supporting their participation in rapid CLATHRIN-dependent endocytic mechanisms that may clear neurotransmitter release sites for subsequent synaptic vesicle priming and refilling of the release-ready vesicle pool.…”
mentioning
confidence: 77%
“…Previous analysis in this model examined the temperature-sensitive (TS) DYNAMIN mutant shibire and revealed a rapid role for endocytic mechanisms in maintaining neurotransmitter release during synaptic activity (15,16). Subsequent work has extended these findings and showed that inhibition of DYNAMIN or AP-2 disrupts fast refilling of the release-ready synaptic vesicle pool (17)(18)(19). The results reported here demonstrate colocalization of CLATHRIN and DAB at the active zone (AZ) and provide functional and ultrastructural evidence supporting their participation in rapid CLATHRIN-dependent endocytic mechanisms that may clear neurotransmitter release sites for subsequent synaptic vesicle priming and refilling of the release-ready vesicle pool.…”
mentioning
confidence: 77%
“…CME is important for both presynaptic and postsynaptic functions and both functions have been implicated in schizophrenia [73][74][75] . In presynaptic axon terminals, CME is required for the retrieval of synaptic vesicle proteins following neurotransmitter release, and for the recycling of vesicles back to the reserve pool 7 . Also, in presynaptic terminals, protein kinase C (PKC)-induced internalization of DAT from the synapse is clathrin-and dynamin-dependent 76 .…”
Section: Altered Cme May Contribute To Synaptic Pathologymentioning
confidence: 99%
“…The route taken is, at least in part, determined by members of the Rab family of GTPases 5 , which are associated with distinct endosomal populations and which are central to ensuring that vesicle cargos find their correct destinations [6][7] .…”
Section: Introductionmentioning
confidence: 99%
“…Similar to nerve terminals, in which endocytosis supports high rates of synaptic vesicle recycling (1,2), neuroendocrine cells undergo vigorous membrane trafficking to regulate large dense-core vesicle (LDCV) release and cellular functions. However, the mechanisms by which endocytosis influences secretory function are unclear, and the molecular nature of endocytosis in these cells remains poorly understood.…”
Section: Introductionmentioning
confidence: 99%